FOLFOXIRI/Bevacizumab Plus Nivolumab as First-Line Treatment in Metastatic Colorectal Cancer RAS/BRAF Mutated: Safety Run-In of Phase II NIVACOR Trial - Damato, Angela; Bergamo, Francesca; Antonuzzo, Lorenzo; Nasti, Guglielmo; Iachetta, Francesco; Romagnani, Alessandra; Gervasi, Erika; Larocca, Mario; Pinto, Carmine (Frontiers in Oncology, 2021)
The NIVACOR trial is a phase II study assessing the efficacy and safety of nivolumab in combination with FOLFOXIRI/bevacizumab in first line setting in patients affected by metastatic colorectal cancer (mCRC) RAS/BRAF mutated. We report safety run-in results in the first 10 patients enrolled. Patients received triplet chemotherapy with FOLFOXIRI scheme plus bevacizumab, in association with nivolumab every 2 weeks for 8 cycles (induction phase) followed by bevacizumab plus nivolumab every 2 weeks (maintenance phase), until progression of disease or unacceptable toxicities. The first ten patients were evaluated: 7 experienced at least one adverse event (AE) related to FOLFOXIRI/bevacizumab and 2 related to nivolumab. The most frequent grade 1-2 AEs related to FOLFOXIRI/bevacizumab were: diarrhea and fatigue (71%), nausea and vomiting (57%); 3(43%) had grade 3-4 neutropenia. 2(20%) patients developed grade 1-2 AEs nivolumab related: skin rash and salivary gland infection. Two patients delayed the dose because of serious AEs, proteinuria and salivary gland infection; one patient discontinued experimental treatment due to the ileo-urethral fistula and concurrent clostridium infection diarrhea. No treatment- related death occurred. The safety run-in analysis of NIVACOR trial reassured using co administration of FOLFOXIRI/bevacizumab and nivolumab resulting well tolerated with an acceptable toxicity profile.